2023
DOI: 10.1371/journal.pgen.1010984
|View full text |Cite
|
Sign up to set email alerts
|

Microtubules oppose cortical actomyosin-driven membrane ingression during C. elegans meiosis I polar body extrusion

Alyssa R. Quiogue,
Eisuke Sumiyoshi,
Adam Fries
et al.

Abstract: During C. elegans oocyte meiosis I cytokinesis and polar body extrusion, cortical actomyosin is locally remodeled to assemble a contractile ring that forms within and remains part of a much larger and actively contractile cortical actomyosin network. This network both mediates contractile ring dynamics and generates shallow ingressions throughout the oocyte cortex during polar body extrusion. Based on our analysis of requirements for CLS-2, a member of the CLASP family of proteins that stabilize microtubules, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 64 publications
(149 reference statements)
0
2
0
Order By: Relevance
“…Many of the outer kinetochore proteins in the fibrous corona are also found in the cytoplasmic linear elements. Although a definitive function of linear elements remains elusive, they have recently been shown to regulate cortical microtubules to control plasma membrane dynamics during polar body extrusion (Quiogue et al, 2023). One interesting possibility is that the microtubule regulatory function of these cortical filaments could contribute to separase relocalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the outer kinetochore proteins in the fibrous corona are also found in the cytoplasmic linear elements. Although a definitive function of linear elements remains elusive, they have recently been shown to regulate cortical microtubules to control plasma membrane dynamics during polar body extrusion (Quiogue et al, 2023). One interesting possibility is that the microtubule regulatory function of these cortical filaments could contribute to separase relocalization.…”
Section: Discussionmentioning
confidence: 99%
“…The kinetochore localization of separase and securin may reflect the local recruitment of separase to the vicinity of anaphase target sites while preventing it from directly interacting with substrates. The linear elements were first observed by staining for HIM-10 (Howe et al, 2001), and subsequently numerous outer kinetochore proteins were also found to localize to them (Hattersley et al, 2016; Monen et al, 2015; Pereira et al, 2018; Quiogue et al, 2023). Similar kinetochore linear element structures were observed in fly and bovine oocytes, suggesting these are widely conserved structures (Gilliland et al, 2007; Wu et al, 2023).…”
Section: Discussionmentioning
confidence: 99%